A descriptive study on development of a transfer learning based fault detection model using 2D CNN for air compressors - Hasan, Moenul; Uddin, A.K.M. Faiyaz; Ghosh, Anoup (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.